Shadow chaser - Law, Jerel (Law, Jerel. Son of angels, 2013)
"Jonah's story comes to resemble a modern-day Job as he's faced with trials that affect his health, strength, relationships, and most-prized possessions. As he and the other quarterlings prepare for mid-term exams, their powers are tested once again in the most fierce battle against Abaddon's forces yet. Will Jonah's faith in Elohim continue to persevere as he fights Abaddon in his hardest battle yet?"--Provided by publisher.